ใยอาหารผงจากส้มและการประยุกต์ - นิธิมา อรรถวานิช (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objective of this research was to study the process and charactenstic of dietary fiber (DF) powder from orange pulp and peel. This research studied two varieties of oranges, Mandanrin and Fremont.Total DF contents o Mandarin pulp, Fremont pulp, Mandarin peel and Fremont peel were 43.85, 39.33, 52.89 and 50.73% dry matter, respectively. The production of DF powder from pulp found that it used two minutes in blanching. Pulp was washed with water (pulp: water3, w/r) A number of washing, 1-6 times, was studied. The results showed that DF contents of both pulp powder and water holding capacity (WHC) of Fremont pulp powder increased of when a number of washing increased (p≤0.05), 5 and 4 times the optimum of washing Mandarin and Fremont pulp. Then, blanched pulp was dried in hot air oven and drying temperatures were studied. The levels of temperature 50, 60, and 70℃. Temperatures effected the WHC of Fremont pulp powder (p≤0.05). The more increase in temperature, the more decrease in WHC. The optimal temperature of both pulp were 50℃. In the production of DF powder from peel, the blanching time was two minutes and the blanched peel powder had better color. To study the drying temperature by hot air oven, the level of temperature were 50, 60, and 70℃. The results showed that, temperature effected the color of Mandarin peel powder (p≤0.05), and the optimal temperature were 50℃ for Mandarin and Fremont. The study of drying method showed that Mandarin peel powder which vacuum drying had better color and WHC than hot air drying (p≤0.05). To reduce the bittemess of Mandarin peel powder, the water extraction was used. pH and temperature were studied separately. The levels of pH were 7, 8, 9 and the levels of temperature were 30, 40, 50 and 60℃. The sensory evaluation showed that the bittemess of extracted peel powder less than control (p≤0.05). The debittemess to by ethanol extraction was studied. Concentration of ethanol was 35, 55, 75 and 95% The results showed that the bittemess were reduced (p≤0.05) The comparison of debittering methods found that debittening by increase pH of sample of to 7 had highest overall acceptable (p≤0.05). To improve the color and odor of extracted peel powder, freeze-drying was used. Freeze dried powder had higher color, odor and overall acceptable than vacuum dried powder (p≤0.05). The types of alkali, NaOH, NaHCO₃, Na₂CO₃ and CaCO₃, were studied. The suitable alkali was Na₂CO₃. Chemical and physical characteristics of DF powder from Mandarin and Fremont pulp showed high content of DF. The pulp DF powder had no odor, bland in taste and high WHC. The peel DF powder had quite high DF content, yellow color, orange odor, little bitter taste and high WHC. Enriched DF cupcakes was acceptable